Lamellar ultra-fine grain dual-phase ferrite/martensitic steel and preparing method thereof - LIU YONGNING; JIANG TAO; GUO SHENGWU; SUN JUNJIE (2018)
The invention relates to a lamellar ultra-fine grain dual-phase ferrite/martensitic steel and a preparing method thereof. The structure heredity phenomenon of an initial martensitic structure in the dual-phase zone heating process is used, ferrite and austenite structures with batten characteristics are obtained after two-phase zone heating, the structure is refined, meanwhile, more phase interfaces are introduced into materials, the grain refining process in the rolling process is accelerated, grain refinement is promoted, materials are heated at the high temperature in the preparing processto enable austenite crystals to be subject to coarsening and air cooling or water quenching to the room temperature to obtain the martensitic structure, then the materials are reheated to a certain temperature between A1 and A3, heat preservation is carried out, multi-pass rolling is carried out, the accumulated rolling-down amount is 40%-70%, the after-rolled materials are subject to air coolingor water quenching treatme